2017
DOI: 10.1101/cshperspect.a022327
|View full text |Cite
|
Sign up to set email alerts
|

Bone Morphogenetic Protein–Based Therapeutic Approaches

Abstract: Bone morphogenetic proteins (BMPs) constitute the largest subdivision of the transforming growth factor (TGF)-β family of ligands and exert most of their effects through the canonical effectors Smad1, 5, and 8. Appropriate regulation of BMP signaling is critical for the development and homeostasis of numerous human organ systems. Aberrations in BMP pathways or their regulation are increasingly associated with diverse human pathologies, and there is an urgent and growing need to develop effective approaches to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
53
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 272 publications
(281 reference statements)
0
53
0
5
Order By: Relevance
“…Significantly, despite the fact that BMP signalling dysregulation has been associated with many pathologies, the only FDA approved use of BMPs at present is that of recombinant ligands delivered in open fractures, vertebral fusion and maxillofacial bone augmentation [ 178 ].…”
Section: Bmps and Liver Fibrosismentioning
confidence: 99%
“…Significantly, despite the fact that BMP signalling dysregulation has been associated with many pathologies, the only FDA approved use of BMPs at present is that of recombinant ligands delivered in open fractures, vertebral fusion and maxillofacial bone augmentation [ 178 ].…”
Section: Bmps and Liver Fibrosismentioning
confidence: 99%
“…A previous study also showed that mTOR signaling modulator suppressed heterotopic ossification formation (Hino et al, 2018); metformin exerted a dual negative regulatory effect on mTOR and BMP signal, and it might inhibit heterotopic ossification through an mTOR-BMP crosstalk signaling network (Wu et al, 2019). Recently, synthetic retinoid agonists, as a new option, has shown promise because it inhibited BMP-mediated heterotopic ossification formation in animal models (Sinha et al, 2016), and retinoid agonist therapy is being examined in patients with a rare, genetic form of heterotopic ossification (Lowery and Rosen, 2018). Thus, application of these factors might inhibit heterotopic ossification and promote tendon healing in tendinopathy and tendon injury models; further studies are needed to verify the effectiveness of these therapies for the management of heterotopic ossification formation during the tendon aging process.…”
Section: Discussionmentioning
confidence: 99%
“…This potent effect of a short in vitro priming period displays how powerful the right combination of progenitor cells and preconditioning followed by stimulation can be. This is of notable interest for pleiotropic growth factors such as BMP ligands, for which the safety has been debated in recent years due to the implantation of supraphysiological doses . The potency of solely in vitro priming on the other hand has shown limited success due to insufficient tissue formation in vivo , likely due to a heterogeneous and noncommitted progenitor population .…”
Section: Discussionmentioning
confidence: 99%
“…This is of notable interest for pleiotropic growth factors such as BMP ligands, for which the safety has been debated in recent years due to the implantation of supraphysiological doses. 26 The potency of solely in vitro priming on the other hand has shown limited success due to insufficient tissue formation in vivo, 27 likely due to a heterogeneous and noncommitted progenitor population. 28 In attempts to overcome this, prolonged differentiation time increases the maturity thus potentially also in vivo tissue formation, but challenges integration at the defect site upon implantation.…”
Section: Discussionmentioning
confidence: 99%